2021
DOI: 10.1177/20503121211001161
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of obstetric danger signs and associated factors among pregnant women in Wolaita Sodo town, South Ethiopia: A community-based cross-sectional study

Abstract: Introduction: Obstetric complications continue to be the major causes of maternal mortality in low- and middle-income countries. Knowledge of women toward obstetric danger signs is an important part of improving maternal and fetal outcomes. However, the reported level of knowledge on obstetric danger signs is low and inconsistent. Methods: Community-based cross-sectional study design was used. Data were collected from randomly selected 740 pregnant women. A pregnant woman said to have good knowledge of obstetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(42 citation statements)
references
References 22 publications
(56 reference statements)
1
25
3
1
Order By: Relevance
“…These kinds of danger signs need to be known by pregnant women from the beginning of pregnancy (Chowdhury & Chakraborty, 2017). This is in line with Bolanko et al (2021), stated that in her research, among respondents had awareness about the danger signs of pregnancy, childbirth and postpartum.…”
Section: Danger Signs Of Pregnancy a Types Of Danger Signs Of Pregnancysupporting
confidence: 80%
See 1 more Smart Citation
“…These kinds of danger signs need to be known by pregnant women from the beginning of pregnancy (Chowdhury & Chakraborty, 2017). This is in line with Bolanko et al (2021), stated that in her research, among respondents had awareness about the danger signs of pregnancy, childbirth and postpartum.…”
Section: Danger Signs Of Pregnancy a Types Of Danger Signs Of Pregnancysupporting
confidence: 80%
“…f. Economy Economy is a large set of interrelated production and consumption activities that help in determining how resources are. Women with low monthly income, have little knowledge about the danger signs of obstetrics compared to women who have a high monthly income, similarly pregnant women with low monthly incomes then have more potential to have less knowledge of the danger signs of pregnancy, and vice versa (Bolanko et al, 2021). In low-income communities such as Indians tend to have the lack of good knowledge, because they are prioritized by needs and to travel to health facilities tend to be less interested (Jungari, 2020)…”
Section: Category Of Knowledgementioning
confidence: 99%
“…34 , 35 A study in South Ethiopia also found primigravida women to be less prepared for pregnancy complications and less knowledgeable of pregnancy danger signs, indicating the gap between multigravida and primigravida mothers. 36 In addition, pregnant women who know their gestational age were 50% less likely to practice self-medication. Pregnant women who know their gestational age are more likely to be alert and their pregnancy is more likely to be planned.…”
Section: Discussionmentioning
confidence: 99%
“…En cambio, en el análisis multivariado, solo las variables: paciente añosa (RP 0,95, IC95% 0,91-0,99, p=0,027) y gestaciones previas (RP 0,73, IC95% 0,69-0,78, p<0,001) fueron estadísticamente significativas. En diversos estudios realizados en África [15][16][17] , se aprecia similar asociación, pues las mujeres con embarazos previos, siendo estas multigestas o multíparas, son siempre quienes tienen un mayor conocimiento y, por ende, una mejor actitud. Esto puede deberse a que han experimentado alguna complicación previa que convierte esa experiencia en conocimiento.…”
Section: Discussionunclassified